Friendship - in several painful lessons - Byrski, Elizabeth (Pan Macmillan Australia, 2013)
In Just Between Us, a host of Australia's best-loved female writers bare all on this age-old quandary: Are female friendships all-natural and nurturing? Or are some more damaging than delightful? And most of all, what happens when female relationships go off the rails? And who is to blame? While falling in and out of romantic love is a well-documented experience, losing a friend rarely gets discussed. Which doesn't mean the pain is less - quite the opposite, as we discover in this extraordinary collection of heartfelt fiction and non-fiction works that put female friendship in the spotlight.